From north to south [Electronic reasource] ; Sudan's displaced he ad home. - Greste, Peter; Integrated Regional Information Networks; LC Gift Collection (Library of Congress) ([Nairobi : IRIN, 2005)
When Sudan's warring factions signed the Comprehensive Peace Agreeme nt in January 2005, millions of southerners displaced by the war starte d to plan the long journey home. But a stark reality awaits these peopl e as they return to a region devoid of services and utterly devastated by war.
Summary from videodisc container.
Not viewed.
Sources used: DVD container; cataloging record from OvOp field offic e.
Camera, editing, and narration by Peter Greste.
In English and Dinka with English subtitles.
Keywords: War -- Sudan; Nonfiction films; Short films